Fighting cyberterrorism with legislative bullet: are we really ready? - Zulhuda, Sonny; Abdul Ghani Azmi, Ida Madieha (International Association of IT lawyers (IAITL), 2013)
National governments around the world have taken legislative steps to provide for stronger measures for fear of being struck by cyber-terrorists. Malaysia is not excluded. This paper examines the nature, scope of cyberterrorism and how it threatens the critical information infrastructure and national security. A brief survey is presented on cyberterrorism laws in the US, UK and Australia. It examines further the recent legislative attempts in Malaysia in countering threats of cyberterrorism with critical analysis and recommendation for improvement.